(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The Mamluks established in the seventh century AH / thirteenth century AD an Islamic state sprawling over the ruins of the Ayyubid state, which included Egypt and the Levant, and its rule spanned more than two and a half centuries ago, its beginning was at the hands of the marine Mamluks and their powerful sultans such as Zahir Baybars, Mansour Qalawun and Nasser Muhammad bin Qalawun, During the era of the caliphs of Nasser Muhammad bin Qalawun, the Mamluk state witnessed the control of senior princes over the rule and increased competition between Turkish and Mamluk Mamluk Mammals, which constituted a factor of the weakness and fall of the Mamluk Maritime state after one of the Circassian princes, a plum, managed to depose a R. Sultan of descendants of al-Nasir Muhammad, and he took the throne in 784 AH / 1382 AD.